Effectivity of Trichoderma harzianum as Bio-fungicide Against Moler Disease and Bio-stimulator of Shallot Growth - Rusita, Icha; Sasongko, Hadi (Journal of Agri-Food Science and Technology, 2020)
Moler disease is the primary disease that disturbs the shallot cultivation. Hence, it is beneficial to have preventive measures to mitigate the risk and to improve growth. The research objective is to know the effectivity of Trichoderma harzianum suspension as a bio-fungicide and bio-stimulator. The study used seven treatments, i.e., immersion of shallot seeds on negative control (distilled water), positive control (synthetic fungicide+ZPT 1g/liter), T.harzianum suspension with different concentrations of 2 ppm, 4 ppm, 6 ppm, 8 ppm, and 10 ppm, assigned in a Completely Randomized Design (CRD). Treatment that results in a significant level will be continued to the Least Significance Different (LSD) 5% test. The observed variables are the intensity of moler disease and the growth of shallot seeds. Experiment results show the significant difference between treatments. The optimal treatment to reduce the percentage of moler disease intensity is the immersion of shallot seeds in 10 ppm-concentrated T.harzianum suspension, while to improve the shallot growth is in 8 ppm-concentrated T.harzianum suspension. The intensity of moler disease has a negative correlation to the plants height and leaves diameter but shows no correlation pattern to the number of leaves, wet weight, dry weight, and length of roots.